Synthesis Methods of Nanocellulose from Various Biomass Sources: A Review - Muhammad Nur Alam (Education and Talent Development Center of Indonesia (ETDC Indonesia), 2026)
Nanocellulose has become a strategic renewable nanomaterial because it combines high specific surface area, tunable surface chemistry, biodegradability, and strong reinforcement ability. This review analyzes synthesis methods of nanocellulose from various biomass sources, particularly agricultural residues, non-wood plants, forestry biomass, and agro-industrial waste. The review focuses on chemical, mechanical, enzymatic, and hybrid extraction strategies, including acid hydrolysis, alkaline and bleaching pretreatment, high-pressure homogenization, ultrasonication, TEMPO-mediated oxidation, deep eutectic solvent pretreatment, ionic liquid-assisted extraction, and bacterial biosynthesis. The synthesis shows that acid hydrolysis remains effective for producing highly crystalline cellulose nanocrystals, while mechanical and enzymatic routes are more relevant for cellulose nanofibrils. Green solvent-assisted and mechano-enzymatic approaches provide better prospects for reducing chemical waste and energy demand, although industrial scalability, product consistency, and techno-economic validation remain major barriers. Biomass composition strongly influences yield, crystallinity, morphology, thermal stability, and dispersibility. Therefore, future nanocellulose production should be designed through feedstock-specific, application-oriented, and environmentally responsible process integration.